2009
DOI: 10.1021/jp908530s
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Gas- and Aerosol-Phase Products from the Photooxidation of Naphthalene

Abstract: The current work focuses on the detailed evolution of the chemical composition of both the gas-and aerosolphase constituents produced from the OH-initiated photooxidation of naphthalene under low-and high-NO x conditions. Under high-NO x conditions ring-opening products are the primary gas-phase products, suggesting that the mechanism involves dissociation of alkoxy radicals (RO) formed through an RO 2 + NO pathway, or a bicyclic peroxy mechanism. In contrast to the high-NO x chemistry, ring-retaining compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
337
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(378 citation statements)
references
References 100 publications
38
337
1
2
Order By: Relevance
“…Kramer et al (2016) suggested that isoprene-derived hydroxyhydroperoxide (ISOPOOH) is an essential contributor to the OP of isoprene SOA, consistent with the results of bulk peroxide measurements using 4-nitrophenylboronic acid assay (NPBA assay) by Jiang et al (2017). Since peroxides have been proposed to be a major component in NSOA (Kautzman et al, 2010), it is essential to determine whether or not these peroxides can account for the remaining OP contribution (McWhinney et al, 2013).…”
Section: Op Contribution From Peroxidesmentioning
confidence: 63%
See 2 more Smart Citations
“…Kramer et al (2016) suggested that isoprene-derived hydroxyhydroperoxide (ISOPOOH) is an essential contributor to the OP of isoprene SOA, consistent with the results of bulk peroxide measurements using 4-nitrophenylboronic acid assay (NPBA assay) by Jiang et al (2017). Since peroxides have been proposed to be a major component in NSOA (Kautzman et al, 2010), it is essential to determine whether or not these peroxides can account for the remaining OP contribution (McWhinney et al, 2013).…”
Section: Op Contribution From Peroxidesmentioning
confidence: 63%
“…After testing for the sensitivities of various peroxides in KI assay (Fig. S4), and following the previous work by Kautzman et al (2010), benzoyl peroxide (Sigma-Aldrich, ≥ 98 %) was chosen to represent peroxides in NSOA and used as standards for mass calibration in this study. All values are reported as mass fraction of peroxides in the total SOA.…”
Section: Quantification Of Peroxides In Soamentioning
confidence: 99%
See 1 more Smart Citation
“…They may also be produced as secondary products of polycyclic aromatic hydrocarbon (PAH) oxidation. Naphthalene (Bunce et al, 1997;Chan et al, 2009;Kautzman et al, 2010;Lee and Lane, 2009;Sasaki et al, 1997), phenanthrene (Lee and Lane, 2010;Wang et al, 2007), and anthracene (Kwamena et al, 2006) all generate their corresponding quinone species (naphthoquinone, phenanthrenequinone, and anthraquinone, respectively) via reaction with gas-phase oxidants. Formation of these species from PAH precursors in the atmosphere could increase the redox activity of ambient particles during photochemical aging in locations with PAH emission sources.…”
Section: Introductionmentioning
confidence: 99%
“…C 2 -C 6 DCAs are mainly secondary, formed in the atmosphere as their anthropogenic and biogenic precursors are oxidized (Kawamura et al, 1996;Claeys et al, 2004; 2.5 and Yasui, 2005). Although some aromatic acids formed from oxidation reactions of volatile and/or semivolatile polycyclic aromatic hydrocarbons (PAHs) have been studied extensively, such as phthalic acid, which is an oxidation product of naphthalene analogues with OH, nitrate radicals, and ozone (Wang et al, 2007), their mechanistic features and other oxidation products (e.g., 2-hydroxybenzoic acid and phthalic anhydride) of PAHs were still poorly characterized (Lee and Lane, 2009;Kautzman et al, 2010). Thus, it is necessary to develop novel analytical methods that can be used to identify possible tracers and help understand the formation mechanisms of secondary organic acid aerosol.…”
Section: Introductionmentioning
confidence: 99%